Long term outcomes from the early days of minimally invasive thymoma surgery for Myasthenia Gravis patients: a follow-up of 19 years - Kaba, Erkan; Özkan, Berker; Kakuturu, Jahnavi; Yardımcı, Eyüp Halit; Erdoğdu, Eren; Çimenoğlu, Berk; Duman, Salih; Toker, Alper (Frontiers in Surgery, 2024)
BackgroundLong-term survival outcomes are crucial for accurately determining the effectiveness of treatment in an indolent disease like thymoma. We aimed to analyze the clinical findings in terms of survival and relapse patterns with a median follow up of 105 months (8.7 years) in patients with thymoma and myasthenia gravis who underwent minimally invasive surgery between 2002 and 2015.MethodsA total of 59 pathologically confirmed Masaoka Stage I and II thymoma patients with Myasthenia Gravis (MG) who underwent minimally invasive thymoma resection were included in this study. Primary aim of this study is to evaluate recurrences, overall and disease free survival in patients with a thymoma and MG in the long run. We also aimed to study the changes in Myasthenia Gravis medication during the follow-up.ResultsThe mean age of the patients was 47.6 +/13.5 years. Seventeen patients were at Masaoka Stage I and 42 were at Masaoka Stage II. The median follow-up time was 105 months. The mean size of the tumor was 3.6 cm +/16.2 cm. Twenty-one patients (35%) received adjuvant radiotherapy. There was no postoperative mortality and median length of hospital stay was 4 days. Two patients developed recurrences both presented with pleural metastases. Eight patients died because of non-oncologic pathologies. 10-year disease free survival and overall survival rates were calculated to 96.6% and 86.4% respectively.ConclusionThe 10-year survival analysis and current myasthenic status of stage I-II thymoma patients with myasthenia gravis who underwent minimally invasive surgery demonstrate that these procedures are both safe and effective.